Inflation curb-yes! Wage-freeze-no! - Krishnan, N. K. (Communist Party publication, 1974)
Articles setting forth the views of the members of the Communist Party of India to the promulgation of the Additional emoluments (Compulsory deposit) ordinance of 1974.